Place – The final frontier: Exploring the outer reaches of collaborative agency using the Japanese concept of Ba. (February 2022) - Robinson, Jennifer L; Renshaw, Phil St J
Scholars within the field of Leadership-as-Practice (LAP) address the way that individuals 'transcend their own immediate embeddedness' to achieve volitional coherence known as collaborative agency. The process of collaborative agency is described as inseparable from LAP, yet it remains a nascent field of enquiry requiring additional empirical research. This article presents an investigation of collaborative agency through an abductive case study using video ethnography and interviews. To interpret our results, we turn to the Japanese ideogram for 'place', known as 'Ba'. Rather than a physical reality, Ba is considered an existential space in which leadership groups weave together to create and ripen collaborative agency. Ba guides us to look across and around a group and its socio-material practice. We find that collaborative agency is trans-subjective in nature and sits on a spectrum on which we identify the outer reaches, from one end where Ba is woven through to the other end, called Collapse. We suggest that the place of leadership is within the warp and weft of collaborative agency, including but not limited to a special place woven in Ba where collaborative agency is high and where the group reports they are able to transcend their individualism.